The impact of the Asian financial crisis with special reference to Sarawak economy and a case study on hotel and construction material producing sectors in Kuching - Rakayah, Hamdan (2002)
This study is an attempt to study the impact of the financial crisis with special reference to Sarawak. In order to analyse the situation in a wider perspective the national and state level impact of the crisis were examined.